Contribution to the knowledge of the genus Cucujus Fabricius (Coleoptera, Cucujidae) from China - Zhao, Ming-Zhi; Zhang, Jin-Kun (Zootaxa, 2019)
Cucujus costatus Zhao & Zhang, new species is described from Guangdong, China. This new species can be easily recognized by the longitudinal elevated carinae on elytra and its strongly convex eyes. Additional records for C. kempi Grouvelle, 1913 and C. elongatus Lee & Pütz, 2008 are added. A key to the known Chinese species of Cucujus Fabricius is given.